Bone Transport for Treatment of Traumatic Composite Tibial Bone and Soft Tissue Defects: Any Specific Needs besides the Ilizarov Technique?. (24th February 2020) - Li, Runguang; Zhu, Guozheng; Chen, Chaojie; Chen, Yirong; Ren, Gaohong
Abstract : Objective . To evaluate the surgical efficacy of bone transport (Ilizarov technique) plus "shortening-lengthening, " "flap surgery, " and "open bone transport" as individualized treatments for traumatic composite tibial bone and soft tissue defects. Methods . We retrospectively analyzed sixty-eight cases (mean age: 35.69 years, (range, 16–65)) treated from July 2014 to June 2017, including 29 middle, 18 distal, and 21 proximal tibial bone defects (4–18 cm, mean: 7.97 cm) with soft tissue defects (2.5 cm × 4.0 cm to 30.0 cm × 35.0 cm after debridement). We adopted the bone transport external fixator to fix the fracture after debriding the defect parts. In the meantime, we adopted the "shortening-lengthening technique, " "flap surgery, " and "open bone transport" as individualized treatment based on the location, range, and severity of the composite tibial bone and soft tissue defects. Postoperative follow-up was carried out. Surgical efficacy was assessed based on (1) wound healing; (2) bone defect healing rate; (3) external fixation time and index; (4) incidence/recurrence of deep infection; (5) postoperative complications; and (6) Association for the Study and Application of the Methods of Ilizarov (ASAMI) score. Results . The mean duration from injury to reconstruction was 22 days (4–80 d), and the mean postoperative follow-up period was 30.8 months (18–54 m). After the repair and reconstruction, 2 open bone transport patients required infected bone removal first before continuing the bone transport treatment. No deep infection (osteomyelitis) occurred or recurred in the remaining patients, and no secondary debridement was required. Some patients had complications after surgery. All the postoperative complications, including flap venous crisis, nail channel reaction, bone nonunion, mechanical axis deviation, and refracture, were improved or alleviated. External fixation time was 12.5 ± 3.41 months, and the index was 1.63 ± 0.44. According to the ASAMI score, 76.47% of the outcomes were good/excellent. Conclusion . The Ilizarov technique yields satisfactory efficacy for composite tibial bone and soft tissue defects when combined with "shortening-lengthening technique, " "flap surgery, " and "open bone transport" with appropriate individualized treatment strategies.